Vaccine allergy: evidence to consider for COVID-19 vaccines. Issue 4 (August 2021) - Nilsson, Lennart; Csuth, Ágnes; Storsaeter, Jann; Garvey, Lene H.; Jenmalm, Maria C.
Abstract : Purpose of review: Whereas the COVID-19 pandemic has changed our lives worldwide, we hope that vaccination can combat the disease. We propose how to evaluate suspected severe allergic reactions to the vaccines so that as many as possible may be safely vaccinated. Recent findings: Rare cases of severe allergic reactions after COVID-19 vaccination have been observed, seemingly at a higher frequency than for other vaccines. Few excipients are likely to have caused these reactions. IgE-mediated reactions to polyethylene glycol (PEG) and its derivatives are the most suspected, albeit hitherto unproven, causes. We suggest to make a diagnosis based on skin tests with PEG and PEG derivatives and that these be considered in relation to the decisions required before the first and the second vaccine dose. A vaccine without these excipients is available, but published data about its side effects are limited. Summary: The underlying immunological mechanisms of the rare severe allergic reactions to the COVID-19 vaccines are poorly understood and need to be clarified. Identifying those who have an undiagnosed allergy to PEG and PEG derivatives is crucial before vaccination, and these substances are found in laxatives, cosmetics and in 30% of all our medications today.